Maximizing Molecular Data From Low-Quality Fluid-Preserved Specimens in Natural History Collections - Bernstein, Justin M.; Ruane, Sara (Frontiers in Ecology and Evolution, 2022)
Over the past decade, museum genomics studies have focused on obtaining DNA of sufficient quality and quantity for sequencing from fluid-preserved natural history specimens, primarily to be used in systematic studies. While these studies have opened windows to evolutionary and biodiversity knowledge of many species worldwide, published works often focus on the success of these DNA sequencing efforts, which is undoubtedly less common than obtaining minimal or sometimes no DNA or unusable sequence data from specimens in natural history collections. Here, we attempt to obtain and sequence DNA extracts from a poorly known snake, Hydrablabes periops. This genus has been suggested as belonging to at least two different families (Natricidae and Homalopsidae) and with no fresh tissues known to be available, museum specimens currently provide the only opportunity to determine this snake’s taxonomic affinity. Although our aim was to generate a target-capture dataset for this snake, to be included in a broader phylogenetic study, results were less than ideal due to large amounts of missing data, especially using the same downstream methods as with standard samples. However, rather than discount results entirely, we used mapping methods with references and pseudoreferences, along with phylogenetic analyses, to maximize any usable molecular data from our sequencing efforts. This resulted in a largely complete mitochondrial genome and 275 nuclear loci (ultra-conserved loci, anchored-hybrid enrichment loci, and a variety of loci frequently used in squamate phylogenetic studies) from a formalin-preserved specimen of Hydrablabes periops from the Field Museum of Natural History collection. We combined these data with previously published genomic and Sanger-sequenced datasets to confirm the familial designation of this taxon, reject previous taxonomic hypotheses, and make biogeographic inferences for Hydrablabes. A second H. periops specimen, despite being seemingly similar for initial raw sequencing results and after being put through the same protocols, resulted in little usable molecular data. We discuss the successes and failures of using different pipelines and methods to maximize the products from these data and provide expectations for others who are looking to use DNA sequencing efforts on specimens that likely have degraded DNA.